2012
DOI: 10.1152/japplphysiol.01575.2011
|View full text |Cite
|
Sign up to set email alerts
|

Exercise modulation of the host-tumor interaction in an orthotopic model of murine prostate cancer

Abstract: The purpose of this study is to investigate the effects of exercise on cancer progression, metastasis, and underlying mechanisms in an orthotopic model of murine prostate cancer. C57BL/6 male mice (6-8 wk of age) were orthotopically injected with transgenic adenocarcinoma of mouse prostate C-1 cells (5 × 10(5)) and randomly assigned to exercise (n = 28) or a non-intervention control (n = 31) groups. The exercise group was given voluntary access to a wheel 24 h/day for the duration of the study. Four mice per g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
130
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(144 citation statements)
references
References 26 publications
11
130
2
1
Order By: Relevance
“…Results indicated that primary tumor growth rate was comparable between groups but expression of prometastatic genes was significantly modulated in exercising animals with a shift towards reduced metastasis (Jones et al, in press-a,2012a). Paradoxically, exercise was associated with significant increases in tumor vascularization, as measured by magnetic resonance blood perfusion imaging, while multiplex ELISAs revealed distinct reductions in plasma concentrations of interleukin-6 and CXCL1 in the exercise group.…”
Section: Mechanisms Underlying the Exercise-prognosis Relationshipmentioning
confidence: 98%
“…Results indicated that primary tumor growth rate was comparable between groups but expression of prometastatic genes was significantly modulated in exercising animals with a shift towards reduced metastasis (Jones et al, in press-a,2012a). Paradoxically, exercise was associated with significant increases in tumor vascularization, as measured by magnetic resonance blood perfusion imaging, while multiplex ELISAs revealed distinct reductions in plasma concentrations of interleukin-6 and CXCL1 in the exercise group.…”
Section: Mechanisms Underlying the Exercise-prognosis Relationshipmentioning
confidence: 98%
“…Since rodent skin and immediate subcutaneous tissue has a very low blood flow (Armstrong & Laughlin, 1985), it is possible that subcutaneously transplanted tumors may actually become hypoxic during exercise. However, studies in which tumors were grown at the site of origin (orthotopic implantation) have reported that low intensity exercise does not affect tumor growth (Jones et al, 2012) and reduces the incidence of metastasis (Cohen et al, 1992). These latter findings are consistent recent observations which showed no evidence of increased metastasis or enhanced primary tumor growth in exercised animals bearing orthotopically implanted prostate tumors (McCullough et al, 2013).…”
Section: The Tumor Microenvironment As a Double Edged Swordmentioning
confidence: 99%
“…After secondary screening, 53 papers were deemed eligible and underwent full review (Figure S1). Classification of papers was as follows: (1) incidence (n=24; 45.3%) (2346), growth (n=33; 62.3%) (24, 26, 34, 37, 39, 40, 42, 4469), and metastasis (n=10; 18.9%) (53, 55, 63, 64, 70–75). …”
Section: Resultsmentioning
confidence: 99%
“…Details of the exercise prescriptions are summarized in Tables 1, 2 and 3. The most common modalities included voluntary running (n=22; 41.5%) (24–28, 31, 33, 35, 42, 43, 51, 52, 55, 57, 64–66, 70, 71, 73–75) forced running (n=25; 47.2%) (26, 29, 3641, 4446, 48, 49, 54, 56, 5860, 63, 67–70, 72, 74) and swimming (n=10; 18.9%) (23, 30, 32, 34, 47, 50, 53, 54, 61, 62). …”
Section: Resultsmentioning
confidence: 99%